Prognostic value of small mother against decapentaplegic expression in human gastric cancer. Issue 1 (1st January 2021) - Zhang, He-Wei; Guo, Ying; Sun, Lin-xiao; Ni, Fu-biao; Xu, Ke
Abstract: Gastric cancer is the fifth most common malignancy in the world with alow 5-year survival rate. To date, no study has investigated the prognostic role of the small mother against decapentaplegic (SMAD) in gastric cancer. The association of SMADs with overall survival (OS) of gastric cancer was analyzed on the online Kaplan-Meier (KM) plotter database. Clinical data such as stage, differentiation, gender, treatment, and Her2 mutation status of gastric cancer patients were analyzed. The (E)-SIS3 was used to inhibit SMAD3 expression in gastric cancer cells, and the effects of SMAD3 on gastric cancer cells were analyzed via real-time cellular analysis (RTCA), flow cytometry, colony formation, and immunofluorescence assay. The results showed that the high expression of three members of SMADs (SMAD1, SMAD2, SMAD4) was correlated with afavorable OS of gastric cancer patients. Meanwhile, SMAD3 expression level indicated highly differentiated cancer. We also observed that surgical treatment was associated with high expression level of SMAD1 and SMAD2. Besides, the effect of Her2 on gastric cancer was not noticeable. Moreover, (E)-SIS3 pharmacological assay revealed that inhibition of expression of SMAD3 suppressed the proliferation and migration ability of gastric cancer cells via inducing apoptosis. Collectively, these results demonstrate that the high expression level of three members of SMADs (SMAD1, SMAD2, and SMAD4) is significantly correlated with favorable OS of gastric cancer patients, which is opposite to SMAD3. Thus, SMADs regulate the differentiation of cancer and can be used to guide treatment decisions. ABSTRACT: uf0001